WAYS TO INCREASE THE EFFICIENCY OF TECHNICAL AND TACTICAL PREPARATION IN HIGH-QUALIFIED BOXERS - Mamatqulov Xusanboy Bakhtiyorovich (Web of Journals Publishing, 2025)
this article analyzes the essence of the process of technical and tactical training of boxers, its content and significance. Also, in the development of technical and tactical skills, the correct planning of the training process, taking into account the peculiarities of the competition's activities and the importance of modern approaches are highlighted. Today, in conditions of increasing competition, the success of a boxer largely depends on his technical and tactical training. the article is devoted to the scientific and practical study of ways to improve the effectiveness of technical and tactical training in highly qualified boxers. Based on the results of the study, the effectiveness of training methodology and innovative approaches was shown
Keywords: Boxing, technical-tactical training, high qualification, training methodology, statistics, combat effectiveness.